Towards a phylogenetic classification of Lychnophorinae (Asteraceae: Vernonieae) - Loeuille, Benoit Francis Patrice (2011)
A phylogenetic hypotesis of American Vernonieae based on three molecular regions (ITS, ndhF, rpl32-trnL) and on a morphological dataset reveals the existence of four main lineages in the group. Three of these lineages correspond, with a few adjustments, to subtribes Chrestinae, Lychnophorinae and Vernoniiae. The last lineage is mainly composed of Lepidaploinae and Elephantopinae. In order to keep the Lychnophorinae monophyletic, two small subtribes (Centratherinae, Sipolisiinae) and three monotypic genera (Albertinia, Blanchetia and Gorceixia) must be to transferred to Lychnophorinae, which has the presence of heliangolide in aerial parts as a synapomorphy. Our results show that syncephaly probably appeared independently three of four times in the course of evolution of American Vernonieae. Special features of these aggregation of heads in each lineage suggest that the formation of syncephalia is related to different biological functions: attractive in Chrestinae, disseminative in Rolandrinae or protective in Lychnophorinae. A phylogenetic analysis of Lychnophorinae was further performed based on a morphological dataset and on four molecular regions (ETS, ITS, ndhF, rpl32-trnL), in order to delimit monophyletic genera in Lychnophorinae, and to achieve a better understanding fo the relationships between the genera of the subtribe. The richest genus of the subtribe, Lychnophora, with 32 describe species, emerged as polyphyletic, involving three main lineages not closely related. Most clades obtained are associated with some existing generic concept and can be defined by a simple combination of morphological characters. Albertinia, Blanchetia and Gorceixia are the most basal lineages, whereas Eremanthus and Lychnophora stricto sensu emerged as the most derived clade, which contains half of the species of the subtribe. However, relationships between the remaining clades persist partially unresolved. Aiming to compare the influence of a hierarchical representation of homology hypotheses on phylogenetic inference, two morphological datasets of American Vernonieae and Lychnophorinae (Asteraceae) have been analyzed using parsimony and three-item analysis. The results widely diverged not only in terms of topology but also in the number of homologies recovered. The three-item analysis appears to retrieve a higher information content fron the original datasets. The already acknowledged high level of homoplasy in Vernonieae morphological data is here confirmed and most of the clades are not supported by synapomorphies. Based on the results of the phylogenetic analyses performed, a new classification of the subtribe Lychnophorinae is here proposed. The subtribes Centratherinae and Sipolisiinae are reduced to synonymy of Lychnophorinae and three genera (Albertinia, Blanchetia, Gorceixia) are transferred to the subtribe. As now circumscribed, Lychnophorinae comprises 18 genera and 104 species distributed mostly in the cerrado, domain of the Brazilian Central Plateau, Oiospermum is synonymized under Centratherum, and Irwinia under Blanchetia. Because Lychnophora as currently circumscribed was shown to be polyphyletic, it is here dismantled into three monophyletic genera: Lychnophora s.s., Lychnocephalus and a new genus described herein, Lychnophorella. 17 new combinations are proposed as well as 10 new synonymies. The descriptions of eight new species of Lychnophorinae are presented: Eremanthus brevifolius, Heterocoma gracilis, H. Robinsoniana, Minasia ramose, Paralychnophora glaziouana, Piptolepis campestris, P. monticola and P. schultziana. The synopsis provides the taxonomic status, data on nomenclatural types, geographical distribution, and taxonomic notes for each species.